Effects of Enhancment Span-60 of Vernonia amygdalina Leaves Extract-loaded Niosomes - Pratiwi, Afrianty; Syahrana, Nur Azizah; Ismail, Isriany; Arsul, Muhammad Ikhlas (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2023)
Introdiction: Niosomes are a promising drug carrier because of their bilayer structure and the fact that they are produced by the self-association of nonionic surfactants and cholesterol in an aqueous phase. Niosomes are non-toxic, biodegradable, and compatible with human cells. Aims: This research aimed to create niosomes from V. amygdalina leaves and investigate how span 60 addition affects niosome properties. Methods: Extraction V. amygdalina using maceration, niosomes synthesized using a thin-film hydration process, and characterization performed by SEM, particle size, polydispersity index, zeta potential, and FTIR. Conclusion: V. amygdalina succesfully to loaded into niosomes. Span-60 with various concentration affected of characterization of niosomes. Increased span-60 increasing particle size, polydispersity index, and %EE.